2013
DOI: 10.1097/rlu.0b013e318281658e
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 18F-FDG PET/CT and 68Ga-DOTATATE PET/CT Imaging in Metastasized Merkel Cell Carcinoma

Abstract: Merkel cell carcinoma (MCC) is a rare but very aggressive neuroendocrine tumor of the skin in elderly patients with higher mortality compared with melanoma. No evidence-based standardized chemotherapy exists for metastasized patients.We report the case of an 87-year-old patient with the history of resection of a large MCC of the parietal scalp planned for radiotherapy and staged with FDG PET/CT showing disseminated distant metastases. Ga-DOTATATE PET/CT revealed more extensive tumor load compared with FDG, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 8 publications
0
20
0
4
Order By: Relevance
“…In the largest series evaluating 20 patients with MCC, 111 indium-octreotide scintigraphy demonstrated a sensitivity of 78 and a specificity of 95%. However, PET/CT imaging with 68 gallium-labelled somatostatin analogues ( 68 Ga-DOTATOC, 68 Ga-DOTATATE) has greater detection efficacy in NETs [54], and recent studies have suggested its accuracy in MCC staging [18,22]. The lack of sensitivity of conventional SRI in MCC patients may be related to the heterogeneity of individual SSTR expression, as evidenced by immunohistochemistry in our study.…”
Section: Discussionmentioning
confidence: 38%
See 1 more Smart Citation
“…In the largest series evaluating 20 patients with MCC, 111 indium-octreotide scintigraphy demonstrated a sensitivity of 78 and a specificity of 95%. However, PET/CT imaging with 68 gallium-labelled somatostatin analogues ( 68 Ga-DOTATOC, 68 Ga-DOTATATE) has greater detection efficacy in NETs [54], and recent studies have suggested its accuracy in MCC staging [18,22]. The lack of sensitivity of conventional SRI in MCC patients may be related to the heterogeneity of individual SSTR expression, as evidenced by immunohistochemistry in our study.…”
Section: Discussionmentioning
confidence: 38%
“…This is supported by the ability of SRI to detect MCCs and their metastases [17,18,19,20,21,22] as well as some cases of tumoural response to somatostatin analogues [23,24,25,26,27,28]. However, the efficacy of SSTR-targeted imaging and therapy in MCC patients is not uniform, suggesting that the in situ expression of SSTRs in MCCs may be heterogeneous.…”
Section: Introductionmentioning
confidence: 94%
“…SLNB can be spared. SSTR-PET may have higher diagnostic performance than FDG-PET in MCC as pointed out in a recent case report [24]. In a retrospective analysis, FDG-PET/(CT) has been shown to be a useful tool in management of MCC and may lead to upstaging of 16% of patients [14].…”
Section: Discussionmentioning
confidence: 99%
“…SSTR-PET is more sensitive and accurate for tumor detection than respective scintigraphic techniques [22]. SSTR-PET has been claimed to be beneficial compared to conventional imaging and FDG-PET in selected patients with MCC [23,24]. …”
Section: Introductionmentioning
confidence: 99%
“…Preliminary case reports have indicated that 67 Ga-DOTATATE can localize well in MCC, with one case showing better localization than FDG [22,24,25]. In order to determine if there is any role for these new 68 Ga PET tracers additional studies need to be performed evaluating their utility in MCC.…”
Section: Molecular Imaging and Therapy Of Merkel Cell Carcinomamentioning
confidence: 99%